2015
DOI: 10.7589/2014-08-202
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of the Causative Agent of White-nose Syndrome on Rafinesque's Big-eared Bats (Corynorhinus rafinesquii) and Two Species of Migratory Bats in the Southeastern USA

Abstract: ABSTRACT:Pseudogymnoascus destructans, the causal agent of white-nose syndrome (WNS), is responsible for widespread mortality of hibernating bats across eastern North America. To document P. destructans exposure and infections on bats active during winter in the southeastern US, we collected epidermal swabs from bats captured during winters 2012-13 and 2013-14 in mist nets set outside of hibernacula in Tennessee. Epidermal swab samples were collected from eight Rafinesque's big-eared bats (Corynorhinus rafines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…The United States Fish and Wildlife Service estimated that >5.5 million individuals died from WNS between the emergence of this disease in 2006 and January 2012 (USFWS 2012) and multiple host species are impacted, but to varying degrees (Turner et al 2011;Langwig et al 2012). DNA from the pathogen has been identified on 12 North American species of bat from six genera and seven of these species have been documented with skin lesions diagnostic of WNS, whereas no skin lesions have been observed on the remaining five species Gargas et al 2009;Chaturvedi et al 2010;Bernard et al 2015; US FWS: https://www.whitenosesyndrome.org/about/bats-affected-wns/). DNA from the pathogen has also been isolated from multiple species of bat throughout Europe and in Asia (Puechmaille et al 2011;Hoyt et al 2016) and lesions characteristic of WNS have been identified in some of these species (Pikula et al 2011;Zukal et al 2014;Hoyt et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The United States Fish and Wildlife Service estimated that >5.5 million individuals died from WNS between the emergence of this disease in 2006 and January 2012 (USFWS 2012) and multiple host species are impacted, but to varying degrees (Turner et al 2011;Langwig et al 2012). DNA from the pathogen has been identified on 12 North American species of bat from six genera and seven of these species have been documented with skin lesions diagnostic of WNS, whereas no skin lesions have been observed on the remaining five species Gargas et al 2009;Chaturvedi et al 2010;Bernard et al 2015; US FWS: https://www.whitenosesyndrome.org/about/bats-affected-wns/). DNA from the pathogen has also been isolated from multiple species of bat throughout Europe and in Asia (Puechmaille et al 2011;Hoyt et al 2016) and lesions characteristic of WNS have been identified in some of these species (Pikula et al 2011;Zukal et al 2014;Hoyt et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in winter behavior associated with WNS have been documented, with bats roosting in exposed regions of cave entrances or leaving hibernacula during the day, and flying during cold winter nights (Turner, Reeder & Coleman 2011;Foley et al 2011;Carr, Bernard & Stiver 2014). To date, seven bat species have been confirmed with the disease via histopathology, with five additional species confirmed with P. destructans DNA on their epidermis (Meteyer et al 2009;USFWS, 2014;Bernard et al 2015).…”
mentioning
confidence: 99%
“…This study is an important baseline metric due to the recent incursion of White Nose Syndrome (WNS) into bat populations of the southeastern US. A recent article reported detection of Pseudogymnoascus destructans, the causative agent of WNS, on bats in Tennessee during 2012-14 (Bernard et al 2015), although detections first appeared in Tennessee during the winter of 2009-10 (US Fish and Wildlife Service 2015). While the geographic scope of this study is limited, the study area includes Great Smoky Mountains National Park, which has the highest number of visitors of any national park in the US.…”
Section: Species Composition Of Submissions Inmentioning
confidence: 99%